PS-B05-4: COMPARATIVE EFFECTS OF RENAL DENERVATION IN DIFFERENT STAGES OF HYPERTENSION ON CARDIAC, RENAL, AND ADIPOSE PATHOLOGY IN DAHL SALT-SENSITIVE RATS. (January 2023) - Nagata, Kohzo; Tagami, Kaito; Okuzawa, Toko; Hayakawa, Misaki; Nomura, Akane; Nishimura, Tomo; Furukawa, Nozomi; Sakabe, Nanako; Ikeda, Katsuhide; Kobuchi, Shuhei; Kitada, Kento; Fujisawa, Yoshihide; et al.
Abstract : Objective: Renal denervation (RDN) has emerged as a novel therapy for resistant hypertension. In Dahl salt-sensitive (DahlS) rats, RDN does not prevent the development of hypertension but attenuates the progression of hypertension. We have now investigated the comparative effects of RDN in early versus advanced stages of hypertension on cardiac, renal, and adipose tissue pathology in DahlS rats. Design and method: Male DahlS rats fed an 8% NaCl diet after 6 weeks of age were subjected to RDN or sham surgery at 7 (early stage) or 9 (advanced stage) weeks. In the RDN groups, all visible nerves along the vessels were cut and the vessels were painted with a solution of 10% phenol in absolute ethanol. In contrast, in the sham-operated groups, the kidneys were exposed but the vessels were not stripped or coated with phenol. At 12 weeks, left ventricular (LV), renal, and adipose tissue were excised for analysis. Results: Successful RDN was confirmed by determination of renal norepinephrine content in each rat subjected to RDN less than 10% of the mean values of those in the sham-operated groups. Although both stages of RDN modestly attenuated blood pressure elevation, they improved LV diastolic function and fibrosis and attenuated macrophage infiltration and expression of monocyte chemoattractant protein-1 (MCP-1) and tumor necrosis factor-α (TNF-α) genes in the heart, to a similar extent. In addition, both stages of RDN similarly reduced macrophage infiltration in glomeruli, the glomerulosclerosis index, the tubulointerstitial injury score as well as expression of MCP-1 and TNF-α genes in the kidney. The early stage group showed reductions in both retroperitoneal fat mass and adipocyte cross-sectional area, whereas the advanced stage group did an increase in fat mass without any change in adipocyte size. Conclusions: Both early and advanced stages of RDN mildly attenuated hypertension as well as ameliorated cardiac and renal injury, to a similar extent, in salt-loaded DahlS rats. The anti-hypertensive effect of RDN is thus likely attributable primarily to improved renal pathology. These results also suggest a possible crosstalk among the kidney, cardiovascular system, and adipose tissue via neural mechanisms in salt-sensitive hypertension.